2019
DOI: 10.4067/s0717-73562019005000301
|View full text |Cite
|
Sign up to set email alerts
|

Estudio Regional Sistemático De Treponematosis en Conchales (Sambaquis) Precolombinos De Brasil

Abstract: En el marco de discusión de las hipótesis sobre el origen de la sífilis (precolombina, colombina y unitaria), este estudio tuvo como objetivo identificar, a través de un trabajo sistemático, casos de treponematosis en individuos excavados en sitios arqueológicos de la costa sureste de Brasil. Se investigaron 768 esqueletos de 45 conchales (sambaquis) utilizando un método morfoscópico integrado para diagnosticar treponematosis en los huesos (sífilis, yaws y bejel). Fueron detectados 22 (2,86%) casos sospechosos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
8
0
5
Order By: Relevance
“…The presence of the treponematoses (yaws, bejel, and syphilis) in America thousands of years before contact is evident and the absence of bejel in South and Central America reinforces the theory of treponematoses dispersion according to the latitude and climate (Filippini et al, 2019). The discrepancy between the number of cases of yaws and syphilis in the American archaeological record could be explained by its pathological characteristics, because bone lesions occur in 33% of yaws infected whereas 1% to 5% of syphilitics have their bones affected (Hackett, 1976; Ortner, 2003).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The presence of the treponematoses (yaws, bejel, and syphilis) in America thousands of years before contact is evident and the absence of bejel in South and Central America reinforces the theory of treponematoses dispersion according to the latitude and climate (Filippini et al, 2019). The discrepancy between the number of cases of yaws and syphilis in the American archaeological record could be explained by its pathological characteristics, because bone lesions occur in 33% of yaws infected whereas 1% to 5% of syphilitics have their bones affected (Hackett, 1976; Ortner, 2003).…”
Section: Introductionmentioning
confidence: 63%
“…In South America, nonspecific cases of treponematoses over 8000 years‐old were found in Chile and Peru, whereas the oldest syphilitic case on the continent was exhumed in “Aguazuque,” Colombia (5030 ± 40 yBP) (de Melo et al, 2010). On the east coast, the oldest case of treponematosis was found in “Piaçaguera” (6342 ± 34 yBP) while the most recent case was in “Praia da Tapera” (425 ± 70 yBP), evidencing the presence of treponematoses in Brazilian shell middens ( sambaquis ) for, at least, 5500 years (Filippini et al, 2019). Treponematoses in adults are relatively well represented in the archaeological record, but CS is quite rare before contact in the Americas, with only two cases described at this moment (Cook & Powell, 2005; Filippini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that JABII individuals presented paleopathological lesions such as treponematoses, which are conditions resulting from infections transmitted through person-to-person contact, also indirectly corroborate to the present finding. Finally, yet significantly, high frequency of paleopathological markers (Filippini et al, 2019) in the JABII inhabitants could have been caused by parasitic infections, probably triggered by poor sanitary conditions and considerable crowding of people.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-nine specimens from Jabuticabeira II from the Laguna region of Santa Catarina on the Brazilian coast, both with and without pathologies, were incorporated in this study. Previous osteological analyses had revealed infection-related pathologies suggesting potential treponemal infections 30 , such as periostitis (24 cases), bone remodelling (4 cases) and moth-eaten marks on the cranium (4 cases). Of the 37 samples considered preliminarily positive for treponemal DNA after the initial screening, 12 were from individuals with pathologies, and the rest came from non-pathological specimens (Supplementary Table 1 ).…”
Section: Geographical Origins and Palaeopathologymentioning
confidence: 99%